Data structures and software development in an object-oriented domain - Tremblay, Jean-Paul; Cheston, Grant A. (Upper Saddle River, New Jersey : Prentice-Hall, 2003)
This first edition book integrates data structures, library design, and software principles into one package. The authors begin with simple software engineering concepts, and repeatedly use them to develop applications throughout the text. The topics covered include fundamental design concepts and principles; object oriented analysis and design; and design for reuse. For computer programmers.
1. State of Software Development -- 2. Java Basics -- 3. Objects and Classes -- 4. Arrays and Strings -- 5. Array Algorithms and Their Analysis -- 6. Abstract Data Types and Their Implementation -- 7. List Fundamentals -- 8. Advanced List Concepts and the Uos Data Structure Library -- 9. Stacks -- 10. Recursion -- 11. Queues and Priority Queues -- 12. Object-Oriented Development: An Example -- 13. Trees -- 14. Elementary Problem Modeling and System Design -- 15. Principles of Software Design -- 16. Software Testing -- 17. Bags, Sets, and Dictionaries -- 18. Sorting -- 19. Graphs -- 20. Files -- A. Java Appendix -- B. Java Data Structure Library -- C. Math Primer.
Includes bibliographical references and index.
Keywords: OBJECT-ORIENTED PROGRAMMING (COMPUTER SCIENCE)